Determining overwintering performance and economic viability of monosex tilapia fingerling production in hapa cum cage aquaculture system for Bangladesh’s haor fishers - Bhuiya, Shahidul Islam; Mondal, Roni Chandra; Kabeer, Fozlul; Alam, AKM Nowsad (Journal of Fisheries, 2023)
Ensuring a consistent supply of uniformly sized fingerlings for tilapia cage aquaculture in Bangladesh’s poses a significant challenge. This study assessed overwintering growth performance and economic viability of monosex tilapia fingerling production in haor waters. Nine hapas, each inside a designated treatment cage, were stocked with T1 (200), T2 (250) and T3 (300) tilapia fry, averaging 1.25±0.25 g, per m³ for 90 days. The most successful treatment continued for two subsequent crops over two years for economic viability assessment. Average final body weight gain was the highest at the lowest stocking density (T1, 58.86±7.23 g), but the most desirable biomass gain (222 kg cage⁻¹) occurred at medium stocking density (T2). Beyond biomass gain, T2 exhibited superior profitability, with 26% and 30% profitability in the second and third crops respectively, over total costs. In conclusion, overwintering tilapia fingerling production in the hapa-cum-cage system at a stocking density of 250 m⁻³ proved more profitable and sustainable than other treatments, offering a viable income-generating option for resource-poor haor fishers.